Preface - Pareek, Chandra Shekhar (Translational Research in Veterinary Science, 2020)
In continue to the previous editions, the second volume and second issue (Year 2019) of the scholarly open-access journal Translational Research in Veterinary Science (TRVS), Nicolaus Copernicus University (NCU) publishers’ is publishing five research papers devoted in the field of veterinary science. This published issue of TRVS includes three manuscripts based on the CNVs, GWAS, veterinary public health, colibacteriosis research studies, and two short communications describing “Omics data report in brief” in cattle.